Comparison of Breast and Abdominal Adipose Tissue Mesenchymal Stromal/Stem Cells in Support of Proliferation of Breast Cancer Cells - Kim, Jaehyup (2013)
In this study, we compared MSCs from breast and abdominal tissue in terms of their expression of genes deemed important in the support of breast cancer growth and their effect on gene profile of macrophages after coculture. In addition, we investigated the role of MSCs, alone or in combination with macrophages, on proliferation of breast cancer cell lines. Our results show that MSCs derived from breast and abdominal adipose tissues have a comparable gene expression profile, have similar effect on gene expression of macrophages, and are comparable in supporting breast cancer cell line proliferation.